Pengaruh Kepemimpinan Transformasional Kepala Daerah Terhadap Kinerja Pegawaidi Sekretariat Daerah Pemerintah Provinsi Maluku Utara - Hi. Laha, Samaun; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2015)
The regional administration is directed to accelerate the realization of public welfare through the improvement ofservice, empowerment, and community participation, as well as increased competitiveness of the region by observingthe principles of democracy, equality, justice, and the peculiarities of an area in the Unitary State of the Republic ofIndonesia. To the head area in demand to improve the quality and not merely rely on institutions and is supported byintellectual ability, sharpness of vision, and the ability of ethical and moral civilized. The issues raised in this study isAre there any significant effect of Transformational Leadership Regional Head Against Employee Performance in theRegional Secretariat of the Government of North Maluku province. This study aims to determine the significant influenceof regional leadership to employee performance in the Regional Secretariat of the Government of North Malukuprovince. In this study, the type of study is a survey research type. The method used is explanatory, as it explains thecausal relationship between the variables through hypothesis testing. This was done to demonstrate a wide range ofdata and theories that have been obtained to then be in the know the level of significance between the discussion ofissues were raised with the reality that has been found, the closer to the type of Quantitative Research. These resultsindicate that the Regional Head of Transformational Leadership, influence the variable (Y) Performance Officer at theSecretariat of the Regional Government of North Maluku province with the number of correlation of 0.25 in the lowcategory but has particularly certainty. This study uses the sample, based on the test of the hypothesis that thesample is proven to represent the population as a whole. In a matter of determination as well as the contribution ofvariable (X) of the variable (Y) is low at 6.25% above the value interpretation. From the test results, the reality in thefield, the hypothesis of this study is: â€œthe influence of Transformational Leadership Regional Head on EmployeePerformance in the Regional Secretariat of the Government of North Maluku province.â€ Has been proven and testedempirically in the field can thus be said that the leadership Gebernur North Maluku, including the leadership styletrasformasional with low category.Recommendations from this study are: (1) In order to leadership which is run by thegovernor can be run with both the need for a courageous stand to think and act in accordance with the applicableprovisions, (2) be more active to transform attitudes in the form of policy making and policy should based on theability to mengaplikasinya, (3) To the employees to work in accordance with scientific qualification in order to improveperformance by improving the quality, quantity and integrity. In addition to realizing the public service is always openand not favoritism.